Land and maritime zones of peace in international law - Subedi, S (1993)
During the past few decades a number of initiatives have been undertaken both inside and outside the UN to establish Zones of Peace (ZOP) in various parts of the globe. Currently, there are seven declarations and proposals for ZOP relative to the Indian Ocean, the South Atlantic, the South Pacific, the Mediterranean, Southeast Asia, Nepal and Tibet. On the basis of the areas they cover and the legal issues they raise, the first four zones are termed in this thesis 'maritime zones of peace1 and the remaining three 'land zones of peace'. The State practice relative to such zones demonstrates a significant move towards the acceptance of a variety of methods of creating different regimes with differing legal content. Yet there has been very little academic discussion on this subject from a legal point of view. Therefore, this thesis is designed to examine the legal aspects of the concept of ZOP. This study begins by examining the State practice on maritime ZOP and looks at whether the concept of maritime ZOP is consistent with the existing principles of international law, especially the freedom of the seas, and whether the State practice on ZOP has crystallised into a rule of customary international law. In doing so, it will assess the legal status of the UN General Assembly declarations on maritime ZOP. This is followed by an examination of the proposals for land ZOP. The study then assesses the extent to which the principles underlying the traditional concepts such as neutrality or demilitarised zones, as well as similar emerging principles, could be applied to the concept of ZOP. Another line of enquiry pursued in this thesis is into the concept of objective regimes in international law. After establishing that there exists in international law a rule on objective regimes, this thesis argues that the regimes of ZOP can be regarded as candidates for objective regimes. It is asserted that the methods applied to the creation of various ZOP are among the internationally accepted methods of creating regimes of a dispositive character and the regime of ZOP is similar to other regimes which have generally been regarded as objective regimes in international law. This thesis finds that although the ZOP is a distinct notion developed in response to the peculiar problems of a single State or a territorial entity or a geographical region, it draws upon similar traditional doctrines as well as other emerging rules of international law. On the whole, the declarations on ZOP can be viewed as innovative methods designed to consolidate the already extant and the emerging rules of international law, accord concrete meaning to certain general principles and apply them in the ZOP concerned.